The Effects of Cross-Cultural Issues on Language Learning in Thai Classrooms - Sipe, Marlon Domagco (HRD Journal, 2013)
English language learning in Thailand has become popular in Thai schools through the years.This mixed qualitative and quantitative study recognizes the incessant infl ux of foreign English teachers,along with the cultural concerns it brings to Thai classrooms. These problems prompted the researcherto investigate various issues that are both benefi cial and disadvantageous to Thai students and foreignteachers. A total of 136 Thai secondary school students in Khon Kaen were surveyed and observed inactual classroom settings, and 50 foreign teachers from 15 countries participated in the survey and13 of them were selected for interview. The surveys were analyzed quantitatively, while the classroomobservation notes and interviews were qualitatively assessed. The fi ndings revealed several themesthat included the common problems that foreign teachers experienced in Thai classrooms, the factorsthat affected the learning interest of Thai students, and the factors that affected the foreign teachers.Ethnicity, discipline and language barrier appeared to be the leading classroom issues among Thaistudents. Keywords : Cross-cultural issues, Language Learning, Socio-cultural Theory, Culture, LanguageAcquisition, Second Language Acquisition